Investigation of the Mechanical Properties of Vinyl ester Carbon Composites Through Immersion in Seawater and Freshwater Using the VARI (Vacuum Assisted Resin Infusion) Method - Nurul Lailatul Muzayadah; Taufiq S. Nurtiasto; Kosim Abdurrahman; Afid Nugroho; Nur M. Ula; Rezky Agung P.; Redha A. Ramadhan; Rozi Hendrawan (National Institute of Aeronautics and Space - LAPAN, 2022)
The carbon-vinyl ester composites have made for the development of the base material for Amphibious floats. The properties of this composite have strength, lighter weight and resistant to corrosion. This study was aimed to report the effect of two different water immersion treatment namely seawater and freshwater on the mechanical properties of composite made from fiber twill and vinyl ester resin using the vacuum assisted resin infusion (VARI) method. Experiments were carried out on tensile, compressive, and shear tests. The specimens were immersed in seawater and freshwater for ten days. The results have shown that Ultimate Tensile Strength of the composite with seawater immersion declined 1.27% compare with the composite without immersion treatment, while the composite in freshwater got greater 3.56%. The decrement of compressive and shear strength was more significant than tensile strength. The compressive strength declined 17.89% and 16.7% for freshwater and seawater treatment, respectively.Â The shear strength decreased 27.87 % and 25.77% for freshwater and seawater treatment, respectively.